Textbook of structural biology - Liljas, Anders; Liljas, Lars; Piskur, Jure; Lindblom, Goran; Nissen, Poul; Kjeldgaard, Morten (Hackensack, NJ : World Scientific, 2009)
Contents: Introduction -- Basics of protein structure -- Basics of nucleic acid structure -- The basics of lipids and membrane structure -- Enzymes -- Metabolism of DNA : replication and recombination -- Transcription -- Protein synthesis : translation -- Protein folding and degradation -- Membrane proteins -- Signal transduction -- Cell motility and transport -- Structural aspects of cell : cell interactions -- The immune system -- Virus structure and function -- Structural biology and the evolution of biomacromolecules.
Includes bibliographical references and index.
Keywords: Proteins -- Structure; Ultrastructure (Biology); Protein folding; Biomolecules -- Structure; Proteins; Cell Communication; Cells -- cytology